The Factors Affecting Surgical Room Nurse’s Compliance in Performing Sterile Handwashing in the Central Surgery Installation of RSUD Banyumas - Isti’anah, Isti’anah; Isnaini, Nur; Reguyal, June Christian G (Proceedings Series on Health & Medical Sciences, 2024)
Background: Surgical site infection, as a part of Healthcare-Associated Infections (HAIs), can be prevented by proper handwashing among the surgical team members. Compliance with handwashing has been proven to reduce healthcare associated infections. Method: This was quantitative research with a descriptive correlation design using a cross sectional approach. A total sampling technique was used with a sample size of 35 surgical room nurses’s in the central surgery installation of RSUD Banyumas who met the inclusion and exclusion criteria. The research instrument was aquestionnare. Data analysis was conducted using the chi-square test. Results: The study result show that the majority of nurses have good knowledge (45,7%), high motivation (77,1%), perceive good supervision (74,3%) and are compliant in performing sterile handwashing (71,4%). There is a correlation between knowledge, motivation and supervision with the compliance of surgical room nurses in performing sterile handwashing in the central surgery installation of RSUD Banyumas. Conclusion: Factor such as nurses knowledge and motivation in the surgical room and supervision from the department head are related to the compliance of surgical room nurses in performing sterile handwashing.